Learning Management System: An Experience and Perception Study from Medical Imaging Lecturers and Scholars in a Private University - Mohd Zain, Norhayati; Mohd Fadil, Noor Fadzliyana; Abdul Hadi, Asma' (International Journal of Interactive Mobile Technologies (iJIM), 2018)
A Learning Management System (LMS) is a virtual interactive medium that modernize the classic classroom interaction in the higher education system. It allows instructors and students to share instructional materials, make class announcements, submit and return course assignments, and communicate with each other online. In KPJ Healthcare University College, Department of Medical Imaging under school of Health Sciences was the first unit that has used LMS actively since 2013. The aim of the study is to determine the perception of Medical Imaging lecturers and scholars on LMS implementation before this system is fully utilized by the university. Using a descriptive study, 200 participants were randomly selected to answer the questionnaire via Google form and 93% responded. Analysis such as frequencies, percentage and statistical analysis were conducted. The results showed that most of the lecturers and scholars have a positive perception on the system implemented. Implication of the results and future improvement are also presented.